Immunologic defects in leprosy patients. I. Evidence of immune aberration of suppressor-T lymphocytes in lepromatous leprosy - Makonkawkeyoon S. (2014)
Immunoregulation in various types of leprosy patients was evaluated in vitro using peripheral blood mononuclear leukocytes (PBML) stimulated with phytohemagglutinin-P (PHA-P) or concanavalin A (ConA) for a cell-mediated immune (CMI) assay or pokeweed mitogen (PWM) for a humoral-mediated immune (HMI) assay. The immune responses were evaluated by a lymphocyte transformation test (LTT) and lymphocyte-mediated cytotoxicity (LMC) for the immunoregulation of CMI, and a reverse hemolytic plaque assay for measuring the plaque-forming cells (PFC) and a sandwich ELISA for measuring IgG concentrations for the immunoregulation of HMI. In LTT with PHA-P or ConA, the mean of the normal controls was not significantly different from the means of the untreated LL, BL, BB, BT, and TT leprosy patients. However, a wide variation of LTT results from BT to LL patients was noted: the LTT results of TT patients and normal controls were less variable. A similar pattern of immune responses was noted when studied by LMC in untreated LL, BL, BB, BT, and TT leprosy patients and normal controls. When the untreated patients and normal controls were studied for PFC, using PBML stimulated with PWM, a very similar pattern of PFC was obtained with the different types of leprosy patients. The immunoregulatory role of lymphocytes in leprosy patients was further evaluated by cell mixing cultures. ConA-stimulated PBML from lepromatous leprosy patients were mixed with normal PBML and then stimulated with PHA-P.(ABSTRACT TRUNCATED AT 250 WORDS)